Current status and effectiveness of mentorship programmes in urology: a systematic review. (4th May 2015) - Hay, Daniel; Khan, Mohammed Shamim; Van Poppel, Hendrik; Van Cleynenbreugel, Ben; Peabody, James; Guru, Khurshid; Challacombe, Ben; Dasgupta, Prokar; Ahmed, Kamran
<x xml:space="preserve">Abstract</x> The objectives of this review were to identify and evaluate the efficacy of mentorship programmes for minimally invasive procedures in urology and give recommendations on how to improve mentorship. A systematic literature search of the PubMed/Medline databases was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. In all, 21 articles were included in the review and divided into four categories: fellowships, mini‐fellowships, mentored skills courses and novel mentorship programmes. Various structures of mentorship programme were identified and in general, mentorship programmes were found to be feasible, having content validity and educational impact. Perioperative data showed equally good outcomes when comparing trainees and specialists. Mentorship programmes are effective and represent one of the best current methods of training in urology. However, participation in such programmes is not widespread. The structure of mentorship programmes is highly variable, with no clearly defined 'best approach' for postgraduate training. This review offers recommendations as to how this 'best approach' can be established.